The Impact of Digital Marketing and Brand Image on Revisit Intention in Cultural Tourism Villages: A Study in Bandung, Indonesia - Hendraningrum, Rr. Adi; Narimawati, Umi; Jusuf, Dewi Indriani; Kuswandi, Dede; Suratman, Dadang; Suratman, Dadang; Suhardiman, Sani (Journal of Posthumanism, 2025)
The purpose of this study is to examine how customer experience, pushing and pulling tactics, and digital marketing affect brand perception and interest in repeat visits in the culturally-based tourist communities surrounding Bandung. In this work, quantitative methodologies with verifiable and descriptive designs were employed, along with structural equation modelling (SEM) for data analysis. 400 respondents who had been to tourist villages were given a questionnaire to complete in order to gather data. The analysis's findings demonstrate that driving and pulling tactics, as well as digital marketing, significantly improve brand perception.. In addition, a good customer experience also contributes to improved brand image and revisit interest. The average score for digital marketing and the driving and attracting strategies is in the "pretty good" category, although there are several indicators that need to be improved, such as the quality of digital content and responsiveness to visitor questions. The conclusion of this study confirms that tourism village managers need to optimize digital marketing strategies and improve customer experience to attract more tourists and encourage repeat visits. Thus, tourism villages can contribute more to the growth of the culture-based tourism sector in Indonesia.